Factors affecting the Quality of Financial Reports: A Value Relevance Based Analysis - Djamil, Nasrullah (Basecamp Economics PubMed, 2023)
This study aims to examine the effect of company size, financial leverage, liquidity, and corporate governance practices on the quality of financial reporting within the context of value relevance. The research focuses on publicly-listed state-owned enterprises (BUMN) from 2017 to 2019. The sample consists of 20 BUMN companies, selected using a purposive sampling method, resulting in a total of 60 observations based on specific criteria. This study utilizes a quantitative descriptive research approach and secondary data for analysis. The primary analytical tool is panel data regression analysis. The findings indicate that the quality of financial reports in the value relevance context is significantly influenced by firm size, financial leverage, liquidity, and corporate governance. The coefficient of determination test shows an adjusted value of 77.5%, indicating that these variables collectively account for 77.5% of the variation in financial report quality in the value relevance approach. The remaining 22.5% is attributed to unexamined variables.